Bringing to light the physiological and pathological firing patterns of human induced pluripotent stem cell-derived neurons using optical recordings - Alich, Therese C.; Röderer, Pascal; Szalontai, Balint; Golcuk, Kurt; Tariq, Shahan; Peitz, Michael; Brüstle, Oliver; Mody, Istvan (Frontiers in Cellular Neuroscience, 2023)
Human induced pluripotent stem cells (hiPSCs) are a promising approach to study neurological and neuropsychiatric diseases. Most methods to record the activity of these cells have major drawbacks as they are invasive or they do not allow single cell resolution. Genetically encoded voltage indicators (GEVIs) open the path to high throughput visualization of undisturbed neuronal activity. However, conventional GEVIs perturb membrane integrity through inserting multiple copies of transmembrane domains into the plasma membrane. To circumvent large add-ons to the plasma membrane, we used a minimally invasive novel dark quencher GEVI to record the physiological and pathological firing patterns of hiPSCs-derived sensory neurons from patients with inherited erythromelalgia, a chronic pain condition associated with recurrent attacks of redness and swelling in the distal extremities. We observed considerable differences in action potential firing patterns between patient and control neurons that were previously overlooked with other recording methods. Our system also performed well in hiPSC-derived forebrain neurons where it detected spontaneous synchronous bursting behavior, thus opening the path to future uses of our approach to other cell types and disease models including Parkinson’s disease, Alzheimer’s disease, epilepsy, and schizophrenia, conditions associated with disturbances of neuronal activity and synchrony.